Konflik Tata Ruang Kehutanan Dengan Tata Ruang Wilayah (Studi Kasus Penggunaan Kawasan Hutan Tidak Prosedural Untuk Perkebunan Sawit Provinsi Kalimantan Tengah) - Eko N Setiawan; Ahmad Maryudi; Ris H purwanto; Gabriel Lele (BHUMI: Jurnal Agraria dan Pertanahan, 2017)
AbstractLaw No. 26 Year 2007 on Spatial Planning (UUPR) mandated that all levels of government administration, ranging from the national, provincial, district/ city are obligated to prepare Spatial Plan (RTR). Until 2012, Central Kalimantan is one of the provinces which have not completed its Spatial Plan; one of the reasons was the lack of spatial integration of forestry spatial planning and provincial spatial planning of Central Kalimantan.The absence of spatial integration of forestry and provincial spatial planning of Central Kalimantan has the implication in triggering conflicts of land use. Forest areas were converted into oil palm plantations without any official procedures. There are 282 units of oil palm companies, occupying 3.9 millions hectares of forest area, with non-procedural procedures to convert forest area into oil palm plantation.To resolve this problem, the Government has revised the regulation of forest conversion by issuing PP No. 60/2012, provides opportunities for oil palm plantations, which under the Law of Forestry located in forest area but based on RTRWP of Central Kalimantan lies on APL or cultivation area, given the opportunity to re-apply the permit/license.  IntisariUndang- Undang No. 26 Tahun 2007 tentang Penataan Ruang (UUPR) mengamanatkan bahwa semua tingkatan administrasi pemerintahan, mulai dari nasional, provinsi, kabupaten/kota diwajibkan menyusun Rencana Tata Ruang (RTR). Kalimantan Tengah sampai dengan tahun 2012 merupakan salah satu Provinsi yang belum menyelesaikan Tata Ruang, salah satu penyebabnya karena belum adanya padu serasi antara tata ruang kehutanan dengan tata ruang Provinsi Kalimantan Tengah.Implikasi dari tidak adanya padu serasi antara tata ruang kehutanan dengan tata ruang provinsi Kalimantan Tengah adalah terjadinya konflik dalam penggunaan ruang, dimana terjadi penggunaan kawasan hutan tidak prosedural untuk perkebunan sawit di dalam kawasan hutan di Provinsi Kalimantan Tengah sebanyak 282 unit perusahaan sawit seluas 3,9 juta hektar.Upaya penyelesaian permasalahan penggunaan kawasan hutan untuk perkebunan sawit di Provinsi Kalimantan Tengah diakukan dengan revisi kebijakan tentang alih fungsi hutan PP nomor 60 tahun 2012 yang memberikan kesempatan bagi perkebunan sawit yang berdasarkan Undang-Undang Kehutanan berada di dalam kawasan hutan namun berdasarkan RTRWP Provinsi Kalimantan Tengah berada di kawasan APL maupun budidaya, diberikan kesempatan untuk mengurus perijinannya.